2022
DOI: 10.1007/s00405-022-07429-0
|View full text |Cite
|
Sign up to set email alerts
|

Informed consent for suspension microlaryngoscopy: what should we tell the patient? A consensus statement of the European Laryngological Society

Abstract: Introduction Informed consent for any surgical intervention is necessary, as only well-informed patients can actively participate in the decision-making process about their care, and better understand the likely or potential outcomes of their treatment. No consensus exists on informed consent for suspension microlaryngoscopy (SML). Materials and methods Informed consent procedures in nine countries on five continents were studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The majority of studies have reported a high level of satisfaction with the surgical outcome Glottoplasty is a safe procedure with a small risk of complications. Like all endoscopic suspension microlaryngeal surgeries, it can be associated with anaesthetic risks, including complications of jet ventilation if utilized; short-term complications such as pain, mucosal trauma, haematoma, and tongue numbness; and rare long-term complications of dental damage and tongue paralysis [35]. The use of surgical lasers carries extra risks of laser burns and the exceptionally rare but possibly lethal airway fire.…”
Section: Wendler's Glottoplasty and Its Modificationsmentioning
confidence: 99%
“…The majority of studies have reported a high level of satisfaction with the surgical outcome Glottoplasty is a safe procedure with a small risk of complications. Like all endoscopic suspension microlaryngeal surgeries, it can be associated with anaesthetic risks, including complications of jet ventilation if utilized; short-term complications such as pain, mucosal trauma, haematoma, and tongue numbness; and rare long-term complications of dental damage and tongue paralysis [35]. The use of surgical lasers carries extra risks of laser burns and the exceptionally rare but possibly lethal airway fire.…”
Section: Wendler's Glottoplasty and Its Modificationsmentioning
confidence: 99%